Pengaruh Relative Advantage, Compatibility, Complexity, Observability Dan Trialability Terhadap Intention To Use Pada E-Wallet Dana - Muhammad Haryo Jatmiko; Imronudin Imronudin (POLITEKNIK LP3I JAKARTA, 2023)
The purpose of this study was to determine the effect of Relative advantage, Compatibility, Complexity, Observability, and Trialability on intention to use. This type of research is quantitative research. The population used in this study were students who used E-wallet Dana users, especially the Surakarta area, who had made online transactions using the E-wallet Dana application. The number of samples used was 162 respondents. The data collection method used in this study was the distribution of questionnaires. The research method used in this study uses SEM PLS. The results of this study relative advantage has a significant effect on the intention to use e-wallet, compatibility has a significant effect on the adoption of mobile payment, complexity does not significantly affect the intention to adopt e-wallet, observability has a significant effect on the intention to use e-wallet services, trialability has a significant effect on the intention to adopt e-wallet. a technology can be adopted and accepted by the community if its relative advantage, compatibility, trialability, and observability characteristics have a high value. This is because these characteristics have a favorable impact on technology adoption. In addition, a technology can also be adopted and accepted by the community if its complexity characteristic has a low value, because this characteristic has a negative effect on technology adoption.Keywords: Relative Advantage, Compatibility, Complexity, Observability, Trialability, Intention to Use